Stone Age “chewing gum” yields 5,700 yearold human genome and oral microbiome - Jensen, T. Z. T.; Niemann, J.; Iversen, K. Højholt; Fotaki, A. K.; Gopalakrishan, S.; Sinding, M.-H. S.; Ellegaard, M. R.; Allentoft, M. E.; Lanigan, L. T.; Taurozzi, A. J.; Nielsen, S. Holtsmark; Dee, M. W.; et al. (Stone Age “chewing gum” yields 5,700 yearold human genome and oral microbiome, 2018)
We present a complete ancient human genome and oral microbiome sequenced from apiece of resinous “chewing gum” recovered from a Stone Age site on the island of Lolland,Denmark, and directly dated to 5,8585,661 cal. BP (GrM13305; 5,007±1 1). We sequenced thegenome to an average depthofcoverage of 2.3× and find that the individual who chewed theresin was female and genetically more closely related to western huntergatherers from mainlandEurope, than huntergatherers from central Scandinavia. We use imputed genotypes to predictphysical characteristics and find that she had dark skin and hair, and blue eyes. Lastly, we alsorecovered microbial DNA that is characteristic of an oral microbiome and faunal reads that likelyassociate with diet. The results highlight the potential for this type of sample material as a newsource of ancient human and microbial DNA.